FORMATION OF PEDAGOGICAL MOTIVATION AMONG STUDENTS IN HIGHER EDUCATION - Lekerova, Gulsim; Kashaganova, Tursunkan; Kidirbayeva, Halima; Zhumakhanova, Roza; Erepbaev, Nurlan; Kemelbekova, Gulnar; Balabekov, Aydarkhan (Revista Inclusiones, 2020)
The study is based on the assumption that pedagogical motivation is an elaborate systemic education, which varies depending on the organization of the educational process in university professional training, so that particular hypotheses put forward in the development scheme require an increment into statistical ones. The findings of the research study on the formation of pedagogical motivation will be of interest to the theory and practice of educational psychology, given that fewer and fewer school leavers choose teaching as a career. The authors conducted a longitudinal study in order to test out the hypothesis according to which dynamic motivation of university students’ educational activities can be provided by different ratios of its structural elements as well as by changing types of educational and cognitive activity in the learning process. The 3-year study involved a sample of students (n = 80) and was based on the